Percutaneous Achilles tenotomy using a 18 gauge needle in the treatment of clubfoot with Ponseti method - Richetta, Silvia; Andreacchio, Antonio; Monforte, Sergio (La Pediatria medica e chirurgica, 2022)
Tenotomy is the final step in the corrective phase for the resolution of residual equinus in the Ponseti method of treating clubfoot. There are several methods for obtaining a complete section of the tendon, ranging from mini-open techniques to percutaneous with a scalpel or percutaneous with a large-gauge needle. Since April 2022, Vittore Buzzi Children’s Hospital has performed 36 percutaneous tenotomies of the Achilles tendon in 24 patients using the percutaneous large-gauge needle technique. When compared to the traditional percutaneous scalpel tenotomy procedure, the use of this procedure has allowed us to reduce operating room time, where we routinely perform this type of surgery to optimize pain control and patient safety during the procedure. The technique has proven to be simple, safe, and effective in obtaining a complete section of the tendon; there have been no reports of excessive bleeding, pseudoaneurysms, or nerve injury. There were no differences in clinical outcome or recurrences of equinus that required reoperation during the average three-month follow-up from the previously used technique.